The Reduction of Nitrogen Fertilizer Rate Shifted Soil Bacterial Community Structure in Rice Paddies - Xiaoqing Qian; Shifan Xie; Rui Hu; Wenhui Zhao; Junfei Gu; Wujian Huang; Fulei Xu (Soil Systems)
In order to achieve reasonable yield while keeping environmental risks low, nitrogen fertilizer reduction has been adopted for in rice cultivation. The response of the soil microbial community structure to this management is not fully understood. In this study, the treatments comprising conventional farming practices (330 kg ha−1), reduced N application (270 kg ha−1 and 300 kg ha−1, respectively), and a control without N application were set up in order to reveal the effects of N application rate on the soil microbial community composition in rice paddies. It was discovered that Proteobacteria, Acidobacteria, Actinobacteria, and Chloroflexi represented the most abundant bacterial phyla in all samples. The assembly of the soil bacterial community differed among the treatments, with NH4+-N, available phosphorus (AP), and organic matter (OM) as key drivers. The reduction of N application by 20% decreased soil NO3− up to 32% and increased the abundance of the total functional pathways, especially those associated with carbon fixation, N, S, and CH4 metabolism, whereas N reduction by 10% increase soil N accumulation and soil bacterial richness. In summary, a reduction of N fertilizer by up to 20% compared to the amount used in traditional practices could most effectively regulate the soil bacterial community composition and increase the predicted functional groups associated with N transformation, while maintaining lower soil nitrogen contents.